Multistrengthening Module-Based Salient Object Detection. (2nd November 2021) - Zhao, Qian; Wang, Haifeng; Dang, Junpeng; Li, Songlin; Chang, Rong; Fang, Yanbin; Zhang, Zhi; Peng, Jie; Yang, Yang
Abstract : Object detection is a classical research problem in computer vision, and it is widely used in the automatic monitoring field of various production safety. However, current object detection techniques often suffer low detection accuracy when an image has a complex background. To solve this problem, this paper proposes a double U-shaped multireinforced unit structure network (DUMRN). The proposed network consists of a detection module (DM), a reinforced module (RM), and a salient loss function (SLF). Extensive experiments on five public datasets and a practical application dataset are conducted and compared against nine state-of-the-art methods. The experiment results show the superiority of our method over the state of the art.